Multilocus Sequence Typing and Antigen Gene Sequencing in the Investigation of a Meningococcal Disease Outbreak - Feavers, Ian M. (American Society for Microbiology, 1999)
Multilocus sequence typing and antigen gene sequencing were used to investigate an outbreak of meningococcal disease in a university in the United Kingdom. The data obtained showed that five distinct Neisseria meningitidis strains belonging to the ET-37 complex were present in the student population during the outbreak. Three of these strains were not associated with invasive disease, and two distinct strains caused invasive disease, including several fatalities. The initial case of the disease cluster was caused by a strain distinct from that responsible for at least two subsequent cases and two cases remote from the university, which were epidemiologically linked to the outbreak. These observations were consistent with pulsed-field gel electrophoresis data, but the sequence data alone were sufficient to resolve the strains involved in the disease cluster. Interpretation of the nucleotide sequence data was more straightforward than interpretation of the fingerprint patterns, and the sequence data provided information on the genetic differences among the isolates.